2022
DOI: 10.3390/su14073980
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Tourism-Related Information Consumption Process of Tourists on Social Networking Sites

Abstract: The current study was conducted to examine the consumption process of tourists through the SIPS model as they experienced tourism-related information and products on social networking sites. Data was collected online from Koreans who have experience in using social networking sites, and a total of 479 responses were used for the data analysis. The statistical package for social sciences 23 and analysis of moment structures 23 were used to evaluate stability, consistency for the measurement items, and to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Other previous studies have established the relationship between social media and tourism sustainable performance [38] [39]. As indicated above, a study by [40] also found a positive correlation between social media us-age and tourism competitive sustainability. Finally, recent evidence by [41] found a positive association between E. Agyapong, J. Q. Yuan Open Journal of Applied Sciences social media platforms and tourist destination decision-making in the form of tourists' information search, reaching target tourists, quality customer service, promoting tourist's destination, and building customer loyalty.…”
Section: Social Mediamentioning
confidence: 61%
“…Other previous studies have established the relationship between social media and tourism sustainable performance [38] [39]. As indicated above, a study by [40] also found a positive correlation between social media us-age and tourism competitive sustainability. Finally, recent evidence by [41] found a positive association between E. Agyapong, J. Q. Yuan Open Journal of Applied Sciences social media platforms and tourist destination decision-making in the form of tourists' information search, reaching target tourists, quality customer service, promoting tourist's destination, and building customer loyalty.…”
Section: Social Mediamentioning
confidence: 61%
“…A tourist village is a form of implementing community-based and sustainable tourism development that can improve the standard of living and equal distribution of people's welfare. The development of tourism villages is driven by natural and cultural potential, traditions and harmonious topography and the original natural environment, with slow economic development (An et al, 2022;Chen et al, 2021;Damanik, 2013). The development of a tourist village through a community empowerment model is expected to be a solution to improve the standard of living of its people.…”
Section: Introductionmentioning
confidence: 99%
“…Several tourism-related processes have been impacted by this, including marketing, destination selection, traveller experiences, and tourist feedback, as well as a variety of tourism subsectors like hospitality, transportation, and tour operators (Frenzel et al, 2022). Tourists are eager to engage in tourism activities right away if they identify with the information they learn through social media without going through the identification process, in contrast to what the SIPS model predicted (An et al, 2022). Finding out how people perceive cities from tweets enables relevant organizations to comprehend the image that cities present on mainstream social media and take targeted actions to shape a positive international image, which can increase the willingness of international tourists to travel and strengthen cities competitiveness in the tourism industry (Garcia-Haro et al The primary aim of this study was to investigate the relationship between social media and tourism, while also bridging the gap between the literature of media and tourism.…”
Section: Introductionmentioning
confidence: 99%